PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Saputra, Alvien Dwi; Kartono, Kartono; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to understand the influence of example non example model to student learning result in natural science. Method used in this research is experimental method, with type nonequivalent control group design. Population in this research is all students grade III elementary school 29 Pontianak City. Sample in this research were students of grade III B (31 students) and III A (32 students). Data collecting technique used is a measurement technique. Data collecting tool used is the test. Based on the results of data analysis, obtained average student learning result of the experimental class was 72,72 while the control class was 68,43. Result of hypothesis test (t-test) using t-test separated varians obtained thitung 2,31 and ttabel 1,67 (significant level (α) = 5% and dk = 61) indicate that thitung bigger than ttabel hence hypothesis research accepted. Based on the calculation the effect size obtained 0,49 (medium chategory). It mean example non example model give influence to student learning result in natural science on grade III of elementary school 29 Pontianak City. Keyword: influence, example non example, learning result.